Pengaruh Kompetensi Sumber Daya Manusia, Modal Sosial dan Modal Finansial Terhadap Kinerja UMKM Kabupaten Purworejo - cherryalivia (Progress, 2024)
This study aims to analyze the influence of HR competency, social capital and financial capital on the performance of MSMEs in Purworejo Regency. The population in this study were MSME actors in the category of micro-industrial processing businesses in Purworejo Regency. The sample used purposive sampling technique with 100 respondents. The variables related to this study are HR competency, social capital and financial capital on MSME performance with multiple linear analysis methods. Based on the results of the multiple correlation of the relationship between the HR competency variable and MSME performance, it was obtained as much as 0.787, the social capital variable on MSME performance was obtained as much as 0.616 and the financial capital variable on MSME performance was obtained as much as 0.798. This means that the three variables have a strong relationship to MSME performance. In conclusion, Human Resource Competence, social capital and financial capital have a positive and significant effect on the performance of MSMEs in Purworejo Regency.